The Replacement of the UV-Curve with a New Measure of Hiring Efficiency - Nils Henrik Schager (The Research Institute of Industrial Economics (IUI), 1985)
In this paper we show that changes in the position of the UV-Curve do not unambiguously reflect changes in labour market adjustment ability. In fact, the UV-Curve is displaced not only when hiring efficiency changes but also when the volume of hiring changes. To identify changes in hiring efficiency, we should use the relation between either the duration of vacancies and the stock of unemployment or, alternatively, the duration of unemployment and the stock of vacancies. These measures are applied to Swedish data and produce interesting new evidence on the hiring efficiency of the labour market in Sweden.
Keywords: J63; J64; 330; UV curve; supply and demand of labour; hiring efficiency; Arbeitsmarkt; Beveridge-Kurve; Theorie